Microprocessor, microcomputer, and their applications - Mukhopadhyay, A. K. (Alpha Science International Ltd., 2007)
This book covers single chip microcomputers (microcontrollers) emphasizing on the architecture, memory organization, programming technique and a large number of programming examples. Interfacing techniques have been explained clearly with the aid of diagrams, charts and tables alongwith the input/output devices and controlling and peripheral devices.